The Correlation between Self-Regulated Learning and Academic Achievement in Arabic Language at Junior High School - Munawarotul Laily; Anyes Lathifatul Insaniyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This correlational study examined the relationship between Self-Regulated Learning (SRL) abilities and Arabic academic achievement among junior high school students. A total of 120 students from MTsN 2 Banyuwangi participated as respondents. Data were collected using a reliable 30-item SRL questionnaire (α = 0.89) and report card scores. The results of the Pearson Product Moment correlation test showed a significant positive relationship between SRL and academic achievement (r = 0.547; p < 0.001). The coefficient of determination (R² = 0.299) indicated that SRL contributed 29.9% to the variation in achievement. These findings indicate that students with better self-regulation skills tend to achieve higher academic achievement in Arabic. Therefore, the integration of SRL strategy training into learning is recommended to support improved learning outcomes.